1993
DOI: 10.1002/app.1993.070471003
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of short sisal fiber‐reinforced polyethylene composites

Abstract: SYNOPSISSisal fibers ( Agave-Veracruz) have been used as reinforcements in low-density polyethylene (LDPE). The influence of the processing method and the effect of fiber content, fiber length, and orientation on tensile properties of the composites have been evaluated. The fiber damage that normally occurs during blending of fiber and polyethylene by the meltmixing method is avoided by adopting a solution-mixing procedure. The tensile properties of the composites thus prepared show a gradual increase with fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 11 publications
3
104
0
9
Order By: Relevance
“…Delignification (bleaching) brought better adhesion between fiber and polymer matrix [4]. Joseph and co-workers [5][6] observed that permanganate treated sisal fiber reinforced low density polyethylene (LDPE) composites showed an enhancement in tensile properties due to the permanganate induced grafting. Researchers [7][8][9] worked on jute fibers/polyolefin composites and reported improved properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Delignification (bleaching) brought better adhesion between fiber and polymer matrix [4]. Joseph and co-workers [5][6] observed that permanganate treated sisal fiber reinforced low density polyethylene (LDPE) composites showed an enhancement in tensile properties due to the permanganate induced grafting. Researchers [7][8][9] worked on jute fibers/polyolefin composites and reported improved properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on the mechanical, rheological, electrical and viscoelastic properties of short fibre reinforced LDPE composites as a 4 function of processing method, fibre content, fibre length and fibre orientation were conducted by Joseph et al [5][6][7][8]. Bisanda and Ansell [9] reported on the effect of silane and alkali treatment on mechanical and physical properties of sisal-epoxy composites.…”
mentioning
confidence: 99%
“…This absorbed energy is a measure of composite materials notch toughness and acts as a tool to study temperature-dependent ductile-brittle transition [17,18]. The impact test results are shown in figure 6.…”
Section: Impact Strengthmentioning
confidence: 99%